Biosynthesis of heme O in intraerythrocytic stages of Plasmodium falciparum and potential inhibitors of this pathway - Simão-Gurge, Raquel M. (2019)
Fil: Fil: Simão-Gurge, Raquel M. University of São Paulo. Institute of Biomedical Sciences. Department of Parasitology; Brazil